A Review on Thermal Analysis of Engine Cylinder Fins for Enhancing Heat Dissipation - Abhay Mishra; Sunil Prabhakar; Dinesh Kumar Rao (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
For many years, researchers worldwide have focused on improving engine efficiency, particularly in automotive applications where engine performance is critical. The longevity of engine components is largely influenced by the thermal stresses they endure during operation. Since ancient times, simple and effective methods of engine cooling have been used, primarily to manage the heat generated by fuel combustion and friction between moving parts. Approximately 30% of the energy produced by the engine is converted into useful work, while the remaining 70% must be dissipated to prevent component overheating. In air-cooled internal combustion engines, fins are added around the cylinder’s edge to enhance heat transfer by increasing the surface area. Analyzing these fins is essential for optimizing heat dissipation. This study aims to evaluate previous research efforts focused on improving the material and geometry of cylinder fins to enhance their cooling efficiency. The engine cylinder, a key component subject to significant thermal stresses and rapid temperature changes, relies on fins to accelerate heat transfer and prevent overheating. Given that increasing surface area improves heat dissipation, thermal analysis of cylinder fins is crucial for understanding how much heat is removed from the engine. However, designing such a complex engine system is challenging. The primary goal of this study is to use ANSYS software to explore modifications in the shape, material, and thickness of cylinder fins to investigate their thermal characteristics and improve cooling efficiency.